PENGARUH AROMATERAPI LAVENDER TERHADAP PENURUNAN DERAJAT KECEMASAN PADA LANSIA DI PANTI WREDHA ST. YOSEPH KEDIRI - KRISTANTI, ERVA ELLI (Jurnal Penelitian STIKES Kediri, 2010)
Background : Everyone will get aging process naturally. Being old, Elderly have changes either bio-psycho-socio-spiritual aspects. These changes of this process cause anxiety.Â  Aromatherapy is considered to be able to decrease anxiety and increase comfort. In this case, research was done about influence aromatherapy of lavender toward decreasing anxiety degree to elderly in Panti Wredha St.Yoseph Kediri. Method : This research showed that majority respondents (more than 90%) in Panti Wredha St. Yoseph Kediri experienced decreasing anxiety degree after having aromatherapy of Lavender. Statistical analysis of â€œt-Testâ€ using SPSS 11.0 with Î± â‰¤ 0.05 showed was influence aromatherapy of Lavender toward decreasing anxiety degree to elderly in Panti Wredha St.Yoseph Kediri. Conclusion : The Conclusion of this research that Aromatherapy of Lavender influenced decreasing anxiety degree to elderly because it gave relax and comfort. This condition made elderly thought clearly to face the stressor. If the stressor were overcome well, it would decrease anxiety degree to elderly automatically became light anxiety even more no anxiety at all.